Examining shift duration and sociodemographic influences on the well-being of healthcare professionals in the United Arab Emirates: a cross-sectional study - Bendak, Salaheddine; Elbarazi, Iffat; Alajlouni, Oumara; Al-Rawi, Sana O.; Abu Samra, Amal M. B.; Khan, Moien A. B. (Frontiers in Public Health, 2025)
ObjectiveProviding quality healthcare is an essential part of the healthcare system. The high workload and night work associated with healthcare providing may result in work-life imbalance among healthcare professionals (HCPs) and in degradation in the quality of care.MethodsThis cross-sectional study aimed to assess the effects of sociodemographic characteristics and shift work on HCPs’ well-being in four large hospitals in the United Arab Emirates using a validated questionnaire.ResultsResponses from 526 participants indicated that 79.2% of them were under the age of 40, 70.2% were females and 50.2% were single or divorced. Responses indicated that many HCPs reported engaging in unhealthy behaviors such as consuming energy drinks (37.3%), smoking (14.2%) and taking stimulant pills (5.7%) with males being more susceptible to these practices compared to females. Results also showed that participants perceived their overall health rate, on the average, to be moderate with one third of participants indicating to be overweight. Moreover, results showed that many participants reported having blood pressure issues (16%), diabetes (8.6%) and/or heart diseases (2.7%), with females more prone to these diseases than males. Another important finding was that most respondents reported sleeping significantly less than the recommended duration and taking too long time to fall asleep. Finally, results revealed that HCPs on 12-h shifts indicated having greater satisfaction but tend to experience more exhaustion levels and worsened health indicators than those on 8-h shifts.ConclusionHCPs work has adverse effects on their well-being especially when combined with working at night. Healthcare implications of the results as well as recommendations to improve the well-being of HCPs based on the findings are given at the end.